Immune Response Of Cattle To Boophilus Annulatus (Acari:Ixodoidea) - Sreekrishnan R (Department of Parasitology, College of Veterinary and Animal Sciences, 1992)
A study was undertaken to assess the nature and degree of development of acquired resistance in calves against the cattle tick Boophilus annulatus. Observations were made mainly on the development of natural resistance against repeat infestations and the effect of artificial immunization using the tick antigen. Tissue reactions induced by the ticks at the site of bite were also studied. The results indicated the development of resistance in the host, which was gradual and varying in degrees. Immunodiffusion test failed to reveal the presence of tick antibodies in the sera of calves after repeated infestations, indicating that easily demonstrable quantities of antibodies are not developed even after repeated infestations. The cellular reactions at the site of tick – bite revealed the development of a resistant reaction at the site of bite. Studies made on artificial immunization using the whole – tick extract gave varying results. However, the immunodiffusion test using sera of immunized calves revealed that there is a steady maintenance of antibody level throughout the infestation period. Thus, the results obtained in the present study indicate that antibodies are developed against the tick Boophilus annulatus in calves on natural infestations and using the tick antigen, and that there is a clear possibility of immunizing calves against B. annulatus artificially.